The Paradox of Islamic Education: A Phenomenological Study of Muslim Communities’ Preference for Islamic Elementary Schools - Hamzah, Mohd Isa; Febriani, Afifah; Akinfolarin, Comfort (Khalifa Journal of Islamic Education, 2024)
Parents’ interest in enrolling their children in Islamic Elementary Schools is remarkably high, even though the cost of attending these schools is relatively expensive. This contrasts with public schools, which are generally free of charge. This study aims to explore and explain why Islamic Elementary Schools are highly preferred by Indonesian Muslim communities, particularly parents. The research employs a qualitative method with a case study approach. Research data were collected through in-depth interviews with five participants, consisting of the principal, teachers, and parents, and analyzed using Miles and Huberman’s Interactive Model. The findings indicate that parents’ interest in sending their children to Islamic Elementary Schools is influenced by three main factors: theological, sociological, and academic. (i) The theological factor refers to parents’ perspectives based on religious considerations. (ii) The sociological factor relates to the growing positive image of Islamic schools in Indonesia. (iii) The academic factor is associated with the schools’ ability to achieve high academic performance among both students and teachers. These results provide preliminary insights for future researchers to examine this issue in different contexts and with broader analytical perspectives.